Large-size high-strength corrosion-resistant magnesium alloy and preparation method thereof
By controlling the content of Al, Zn, and Mn in the magnesium alloy, and adopting a multi-step process of hot extrusion, rotary forging and aging heat treatment, the problems of low strength, high cost and low processing efficiency of magnesium alloy rods are solved, and the preparation of large-size high-strength corrosion-resistant magnesium alloys is realized.
Patent Information
- Application Number
- CN202510024943.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-05-02
AI Technical Summary
After forming, the existing magnesium alloy rods have coarse grains, low strength, high preparation cost, and low processing efficiency, making it difficult to meet the needs of large-size high-strength corrosion-resistant magnesium alloys.
A large-size high-strength corrosion-resistant magnesium alloy was prepared by a multi-step process of hot extrusion forming, rotary forging deformation and aging heat treatment.
It realizes the ultra-high strength and excellent corrosion resistance of magnesium alloy rods, reduces production costs, improves processing efficiency, and is suitable for deformation processing and strengthening of large-size magnesium alloys.
Smart Images

Figure CN119913406A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nonferrous metal materials and processing, and relates to a large-size high-strength corrosion-resistant magnesium alloy and a preparation method thereof. Background Art
[0002] Compared to other metals, magnesium has lower density, higher specific strength, and higher specific stiffness, making it widely used in the lightweight production of structural parts. However, as a metal with a close-packed hexagonal crystal structure, magnesium has a relatively small number of slip systems at room temperature, resulting in poor ductility and low absolute strength, which significantly limits its application in production and daily life. To address the poor plastic forming ability of magnesium alloys, traditional magnesium alloy bars are primarily produced using hot extrusion, a process that ensures good forming quality and dimensional accuracy. For example, patent CN117488155A proposes a magnesium alloy bar for automotive parts. The bar's composition is 5.5-7.0% Al, 1.5-3.5% La, 0.4-0.8% Zn, and 0.02-0.06% Sr, with the remainder being magnesium and other impurities. The resulting magnesium alloy bar has a diameter of 10-14 mm, a tensile strength of 287-345 MPa, a yield strength of 220-310 MPa, and an elongation of 6-13%. However, due to the large deformation resistance and slow extrusion speed during the extrusion process, the processing efficiency is low, making it difficult to meet the needs of large-scale processing and forming. At the same time, after hot extrusion, the anisotropy of the material's mechanical properties due to the formation of texture can easily lead to low shear strength of the material. In order to form and prepare larger-sized magnesium alloy bars, higher hot extrusion temperatures are required. However, hot extrusion at higher temperatures will result in coarse grains in the bar structure after forming, and the forming and strengthening effect is not high, making it difficult to meet the demand for high-strength magnesium alloy bars.
[0003] Patent CN118813998A proposes a magnesium alloy comprising the following elements by weight: 4-6% Li, 1.5-2.5% Al, 0.5-1.5% Zn, and the balance Mg, with the combined Al and Zn content being ≤3%. The preparation method comprises: first, smelting the alloy raw materials to obtain an alloy ingot; then, homogenizing the resulting alloy ingot; and then hot-extruding the resulting homogenized alloy at a temperature of 150-250°C and an extrusion ratio of 16-25 to obtain a magnesium alloy rod; and finally, performing multiple rotary forging passes with a deformation of 1-6% per pass and a total deformation of 30-80% to obtain an ultra-high-strength magnesium alloy. The advantage of this patent lies in the improved strength of the magnesium alloy through grain refinement through controlled extrusion and rotary forging. However, due to the high cost of lithium metal and the relatively low content of Al and Zn, the alloying components that provide the primary precipitation strengthening effect, this patent leaves room for improvement in terms of reducing process costs and further improving performance.
[0004] Patent CN117947323A discloses a high-strength, high-toughness Mg-Al-La-Gd-Zr heat-resistant magnesium alloy and its preparation method. The alloy's components and their mass percentages are: Al 4.5-5.0%, La 3.8-4.2%, Gd 0.5-1.0%, Zr 0.4-0.6%; impurity elements include Fe <0.005%, Cu <0.015%, Ni <0.002%, Mn <0.1%, Sn <0.1%; the remainder is Mg. Although this patent utilizes the electronegativity differences of metallic elements to regulate the precipitation of a second phase, improving the morphology and distribution of the second phase at grain boundaries and the heat resistance and plasticity of the magnesium alloy, the resulting magnesium alloy still lacks strength. Furthermore, the addition of rare earth elements leads to a high overall preparation cost, leaving room for improvement in reducing process costs and further improving performance.
[0005] Patent CN114318187A discloses a biomedical high-purity, high-strength, and corrosion-resistant Mg-Zn-Mn magnesium alloy wire and preparation method. The method comprises the following steps: hot extruding a high-purity Mg-Zn-Mn magnesium alloy ingot to obtain an extruded rod; performing a recrystallization annealing treatment on the extruded rod to obtain a recrystallized annealed rod; and sequentially performing a first rotary swaging deformation treatment and a second rotary swaging deformation treatment on the recrystallized annealed rod to obtain the biomedical high-purity, high-strength, and corrosion-resistant Mg-Zn-Mn magnesium alloy wire. Although this patent utilizes extrusion combined with annealing and multiple rotary swaging deformation to produce magnesium alloy wire, the resulting magnesium alloy is relatively small in size, and the second phase strengthening contribution of the magnesium-zinc alloy is insufficient, resulting in poor hot workability and insufficient corrosion resistance, making it difficult to meet the demand for large-sized corrosion-resistant magnesium alloy rods.
[0006] Patent CN107236886A discloses a medical, biodegradable, high-strength, toughness, and corrosion-resistant multi-element Mg-Zn-Y-Ca-Zr alloy and its preparation method. It is a magnesium alloy composed of Mg, Zn, Y, Ca, and Zr, and its chemical composition by mass percentage is: Zn 2.0-6.0%, Y 0.4-1.2% (Zn / Y is 5:1), Ca 0.3-0.9%, Zr 0.5-0.7%, and the rest is Mg; the ingot is manufactured using a full-process gas-shielded resistance furnace melting + rotating magnetic field and ultrasonic external field composite treatment technology, and then undergoes homogenization treatment and hot extrusion deformation to obtain an extremely uniform and fine MgZn2, Mg3YZn6, and Ca2Mg6Zn3 second phase dispersed on the magnesium matrix, thereby obtaining a biomedical magnesium alloy with excellent high strength, toughness, corrosion resistance, and complete degradability. However, this patent does not use large-sized magnesium alloy bars for forming, so the prepared magnesium alloy bars are relatively small in size and still lack strength, making it difficult to meet the demand for large-sized, high-strength magnesium alloy bars.
[0007] Patent CN118497577A discloses a method for preparing a high-strength rare earth magnesium-based composite material and its product. Specifically, the method involves first manufacturing an ingot from spherical TA1 titanium alloy powder and a Mg-Gd-Y-Zr alloy. The resulting ingot is homogenized and then extruded to produce a rod. The rod is then subjected to rotary swaging and finally aging. However, the addition of a large amount of rare earth elements and the use of composite magnesium preparation in this patent result in a relatively high overall production cost. Summary of the Invention
[0008] The purpose of the present invention is to provide a large-size high-strength corrosion-resistant magnesium alloy and its preparation method in order to overcome at least one of the defects of the above-mentioned prior art, such as coarse grains and low material strength of traditional magnesium alloy bars after forming, high preparation cost of high-strength magnesium alloy bars, poor corrosion resistance and low processing efficiency of magnesium alloy bars due to size effect. The present invention realizes the deformation processing and strengthening effect of large-size magnesium alloys, gives the magnesium alloy ultra-high strength and excellent corrosion resistance.
[0009] The purpose of the present invention can be achieved by the following technical solutions:
[0010] One of the technical solutions of the present invention is to provide a large-sized, high-strength, corrosion-resistant magnesium alloy, which comprises the following components in percentage by mass:
[0011] Al 5-10wt.%, Zn 0.1-3wt.%, Mn 0.05-0.5wt.%, impurity element content ≤ 0.1wt.%, balance Mg;
[0012] The magnesium alloy ingot is subjected to hot extrusion forming, rotary forging deformation and aging heat treatment to obtain a large-size high-strength corrosion-resistant magnesium alloy.
[0013] As a preferred technical solution, the magnesium alloy includes the following components in mass percentage:
[0014] Al 6-9wt.%, Zn 0.2-1wt.%, Mn 0.12-0.4wt.%, impurity element content ≤0.1wt.%, and the balance is Mg.
[0015] One of the technical solutions of the present invention is to provide a method for preparing the large-size, high-strength, corrosion-resistant magnesium alloy, which comprises the following steps:
[0016] S1. After melting the raw materials of each element according to the proportion, the raw materials are fully stirred, allowed to stand and heat-insulated, and then refined to achieve purification, degassing, and slag removal. The raw materials are allowed to stand and heat-insulated again, and then the molten metal is cast to obtain an ingot;
[0017] S2. Performing homogenization heat treatment on the ingot, keeping the temperature, homogenizing the alloy composition through atomic diffusion, eliminating dendrite segregation while improving the second phase distribution, and improving the strength and plasticity of the magnesium alloy ingot;
[0018] S3. Preheating the ingot and keeping it warm to improve the plastic deformation ability of the magnesium alloy by high temperature and reduce the resistance to subsequent extrusion deformation. Then, hot extrusion forming is performed to achieve grain refinement through dynamic recrystallization mechanism and form extrusion texture through extrusion deformation, thereby effectively improving the strength of the magnesium alloy and the subsequent processing deformation ability, and obtaining a magnesium alloy extruded bar with excellent performance;
[0019] S4, performing rotary forging deformation along the radial direction of the extruded bar to further improve the strength and corrosion resistance of the magnesium alloy bar by twinning, refine the grain structure, and strengthen the dislocation to obtain a rotary forged bar;
[0020] S5. Perform aging heat treatment on the rotary forging bar and keep it warm. Improve the post-forging microstructure and mechanical properties of the magnesium alloy bar through low-temperature recovery and aging precipitation to obtain a large-size high-strength corrosion-resistant magnesium alloy.
[0021] As a preferred technical solution, the raw material in step S1 is a single substance or an alloy.
[0022] Furthermore, in step S1, the stirring temperature is 700-760° C., the rotation speed is 500-800 rpm, the time is 5-20 min, and the standing time is 20-60 min.
[0023] As a preferred technical solution, in step S1, the stirring temperature is 720-740° C., the rotation speed is 600-700 rpm, the time is 10-15 min, and the standing time is 30-50 min.
[0024] Furthermore, the refining temperature in step S1 is 700-740°C, the added refining agent is selected from one or more of calcium chloride (CaCl2), barium chloride (BaCl2), calcium fluoride (CaF2), and barium fluoride (BaF2), the ratio of the mass of the added refining agent to the total mass of the raw materials of each element is 1:(30-70), the refining time is 5-15 minutes, and the standing time is 20-60 minutes.
[0025] As a preferred technical solution, the refining temperature in step S1 is 710-730°C, the added refining agent is selected from one or more of calcium chloride and barium chloride, the ratio of the mass of the added refining agent to the total mass of the raw materials of each element is 1:(40-60), the refining time is 8-12 minutes, and the standing time is 30-50 minutes.
[0026] Furthermore, the temperature of the homogenization heat treatment in step S2 is 380-420° C., and the holding time is 2-24 hours.
[0027] As a preferred technical solution, the temperature of the homogenization heat treatment in step S2 is 390-410° C., and the holding time is 4-12 hours.
[0028] Furthermore, the temperature of the preheating treatment in step S3 is 380-420° C., and the holding time is 1-4 hours.
[0029] As a preferred technical solution, the temperature of the preheating treatment in step S3 is 390-410° C., and the insulation time is 2-3 hours.
[0030] Furthermore, in step S3, the temperature of the hot extrusion forming is 380-420° C., the extrusion ratio is (5-70):1, and the profile extrusion speed is 0.2-2 mm / s.
[0031] As a preferred technical solution, the temperature of the hot extrusion molding in step S3 is 390-410°C, the extrusion ratio is (5-40):1, and the profile extrusion speed is 0.2-0.6 mm / s.
[0032] Furthermore, in step S3, the grain size of the extruded rod is 5-50 μm, and the rod diameter is Φ30-120 mm.
[0033] As a preferred technical solution, the grain size of the extruded rod in step S3 is 10-30 μm, and the rod diameter is Φ35-75 mm.
[0034] Furthermore, in step S4, the temperature of the rotary forging deformation is 10-250°C, the deformation amount of a single pass is 1-8%, the total deformation amount is 10-45%, the forging speed is 1000-3000 times / min, the feed speed is 1-3m / min, and the mold rotation speed is 150-300rpm.
[0035] As a preferred technical solution, the temperature of the rotary swaging deformation in step S4 is 25-200°C, the deformation amount of a single pass is 2-6%, the total deformation amount is 15-30%, the forging speed is 1500-2500 times / min, the feed speed is 1-2m / min, and the mold rotation speed is 200-250rpm.
[0036] As a preferred technical solution, the deformation amount of a single pass of the rotary forging deformation in the magnesium alloy in step S4 is inversely proportional to the second phase content in the structure. When the Al content is ≥8wt.%, the deformation amount of a single pass is ≤3%.
[0037] Furthermore, the temperature of the aging heat treatment in step S5 is 100-200° C., and the holding time is 24-100 hours.
[0038] As a preferred technical solution, the temperature of the aging heat treatment in step S5 is 150-175° C., and the holding time is 68-72 hours.
[0039] This invention has designed and developed a low-density, high-strength, large-size, and highly uniform magnesium alloy bar. This overcomes the limitations of traditional processing methods for magnesium alloys, which are limited to thermal deformation, and provides a high-strength magnesium alloy and bar processing method that is easily deformable, highly efficient, and inexpensive to produce. The magnesium alloy produced by this method exhibits low density and ultrahigh strength, a uniform structure, fine grain size, and a uniform distribution of numerous twins and fine secondary phases. The ultrahigh strength of the magnesium alloy is achieved through the synergistic effects of multiple strengthening methods, including solid solution strengthening, grain refinement, precipitation strengthening, high-density dislocation strengthening, and twinning strengthening.
[0040] The magnesium alloy rod of the present invention forms a fine-grained structure containing a large number of twins, and after aging heat treatment, partial dynamic recovery and second phase dispersion precipitation can be achieved, ultimately obtaining a magnesium alloy rod with a yield strength of ≥360 MPa, a tensile strength of ≥390 MPa, and an elongation after fracture of ≥2%. At the same time, the magnesium alloy rod has excellent corrosion resistance, with a salt spray corrosion rate of ≤0.1 mm / y.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) Based on the comprehensive composition design of deformable phase and hard phase: The present invention selects the content of Al to be controlled at 5-10wt.%, so that 70-80% of Al and Mg are solid-dissolved to form a banded or granular strengthening phase Mg. 17 Al 12 These low melting point phases can generally deform or break during deformation. Too much Al content will lead to the formation of blocky strengthening phases, while too low Al content will lead to a small number of strengthening phases, which will weaken the strengthening effect on the magnesium matrix. Therefore, the present invention comprehensively balances the Al content in the magnesium alloy and regulates the optimized Mg 17 Al 12 Phase strengthening effect; In addition, the introduction of trace elements such as Zn and Mn into magnesium alloys is also considered to form a small amount of high-melting-point hard second phases such as Al2Zn and Al8Mn5 with the remaining Al, which can play the role of plugging dislocations and promoting matrix deformation strengthening during deformation, thereby improving the strengthening effect. However, these phases should not be too much to prevent deformation cracking caused by excessive hard phases;
[0043] (2) Cold forming process design based on material deformation ability: The multi-directional stress state controlled by multiple passes during the rotary forging process is beneficial to the forming of magnesium alloys, breaking through the traditional deformation process that magnesium alloys, as close-packed cubic structure metals, can only be hot-deformed at high temperatures; the trace elements in the alloy of the present invention react with Al to easily segregate at the grain boundaries, thereby promoting the initiation of non-basal slip, so a rotary forging process with a single-pass deformation of 1-8% and a total deformation of 10-45% can be selected to achieve large-scale deformation processing and strengthening effects of magnesium alloys at room temperature of 10-250°C or low heating temperature conditions; if the deformation of a single rotary forging pass is too large, it is easy to cause cracking and breakage of the magnesium alloy bar during deformation, while if the deformation is too small, the deformation strengthening effect cannot be fully achieved;
[0044] (3) Use deformation and heat treatment to coordinate the transformation of the organization: Initially, the appropriate amount of Al provides a strong solid solution strengthening effect. After deformation, a large number of twins are generated in the organization, which is equivalent to a large number of crystal interfaces. After that, through low-temperature aging treatment, the aging process makes the precipitated Mg 17 Al 12 The phases disperse and precipitate in a short time, while the appropriate temperature ensures that the precipitated phases are not too coarse. Moreover, the partial dynamic recovery still maintains most of the deformation strengthening in the magnesium alloy. Ultimately, a unique magnesium alloy ultrafine-grained structure is formed. Through the combined action of multiple strengthening mechanisms such as grain refinement strengthening, deformation strengthening, and second-phase precipitation strengthening, the magnesium alloy is endowed with ultra-high strength. At the same time, the Al element is evenly distributed in the alloy structure, microgalvanic corrosion is weak, and its corrosion resistance is excellent.
[0045] (4) Low production cost: The use of low-priced alloy raw materials has low cost and simple and reliable process methods. The room temperature or low heating temperature rotary forging process reduces the difficulty of deformation and the requirements for equipment, making the overall structure of the bar uniform and having the potential for large-scale commercial production;
[0046] (5) High processing and production efficiency: The extrusion and rotary forging processes used have the conditions for continuous production, and can realize streamlined operations from material preparation, heat treatment to plastic deformation. The process is simple, the processing precision is high, the performance is reliable, and it has extremely high processing and production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Schematic diagram of microstructure evolution and strengthening during the preparation of a large-scale, high-strength, corrosion-resistant magnesium alloy according to an embodiment of the present invention;
[0048] Figure 2 This is a surface optical microstructure diagram of the rotary swaging bar in Example 1 of the present invention;
[0049] Figure 3 This is a surface optical microstructure diagram of the large-sized high-strength corrosion-resistant magnesium alloy rod in Example 1 of the present invention;
[0050] Figure 4 This is a surface scanning electron microscope (SEM) image of the large-sized high-strength corrosion-resistant magnesium alloy bar in Example 1 of the present invention;
[0051] Figure 5 This is a surface optical microstructure diagram of the rotary swaging bar in Example 2 of the present invention;
[0052] Figure 6 This is a surface optical microstructure diagram of the rotary swaging bar in Example 3 of the present invention;
[0053] Figure 7 This is a surface optical microstructure diagram of the rotary swaging bar in Example 4 of the present invention;
[0054] Figure 8 This is a surface optical microstructure diagram of the rotary swaging bar in Comparative Example 1 of the present invention;
[0055] Figure 9 This is a surface optical microstructure diagram of the swaged bar in Comparative Example 2 of the present invention;
[0056] Figure 10 This is a surface optical microstructure diagram of the rotary swaging bar in Comparative Example 3 of the present invention;
[0057] Figure 11 Graphs showing engineering stress-strain curves of magnesium alloy bars in the embodiments of the present invention and the comparative examples;
[0058] Figure 12 This is a photograph of the high-strength, corrosion-resistant magnesium alloy in Example 1 of the present invention before neutral salt spray corrosion;
[0059] Figure 13 This is a photograph of the high-strength, corrosion-resistant magnesium alloy in Example 1 of the present invention after neutral salt spray corrosion. DETAILED DESCRIPTION
[0060] The present invention is described in detail below with reference to specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0061] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0062] Example 1:
[0063] A high-strength, corrosion-resistant magnesium alloy comprising the following components in percentage by mass:
[0064] Al 8.24wt.%, Zn 0.39wt.%, Mn 0.28wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0065] The large-scale deformation preparation method of the above-mentioned high-strength corrosion-resistant magnesium alloy has the following specific steps:
[0066] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0067] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0068] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ60 mm;
[0069] S4. Rotary forging is performed along the radial direction of the extruded bar at 25° C., with the deformation of each pass controlled at 3% and the total deformation at 22%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0070] S5. Perform aging heat treatment on the rotary forging bar at 175° C. and keep the temperature for 72 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0071] like Figure 1 As shown in the figure, the magnesium alloy rod undergoes dynamic recrystallization during the hot extrusion process, the microstructure is a completely recrystallized structure, the grain structure is relatively uniform, and the corrosion resistance and plastic deformation ability of the magnesium alloy are effectively improved; after rotary forging deformation, the intense high-frequency forging process introduces a large number of twins into the structure, providing the rod with strong fine grain strengthening and dislocation strengthening effects; during the aging heat treatment process, the second phase is dispersed and precipitated on the grain boundaries and twin boundaries, effectively improving the strength and corrosion resistance of the magnesium alloy.
[0072] like Figure 2 As shown, the rotary forging deformation process in Example 1 introduces high-density dislocations into the magnesium alloy rod structure, effectively refines the grain size, and improves the strength of the rod.
[0073] like Figure 3 and Figure 4 As shown in the figure, the large-size high-strength corrosion-resistant magnesium alloy bar obtained in Example 1 contains a large amount of dispersed precipitated Mg 17 Al 12 Phase, effectively improving the strength and corrosion resistance of the bar.
[0074] The mechanical properties data of the above-mentioned high-strength corrosion-resistant magnesium alloy rods are shown in Table 1.
[0075] Table 1 Comparison of alloy composition, swaging process and mechanical properties of the examples and comparative examples
[0076]
[0077] like Figure 11 As shown in Table 1, the large-size high-strength corrosion-resistant magnesium alloy bar finally obtained in Example 1 has a yield strength of 430.1 MPa, a tensile strength of 460.2 MPa, and an elongation after fracture of 2.34%, and exhibits good mechanical properties.
[0078] The corrosion resistance of the plate-shaped samples cut from the above-mentioned high-strength corrosion-resistant magnesium alloy rods was tested by salt spray testing. The neutral salt spray test conditions were:
[0079] 5wt.% sodium chloride (NaCl) solution is continuously sprayed, the salt spray concentration is 50±5g / L, the pH value is 6.5-7.2, the spray pressure is 70-170kPa, the salt spray chamber temperature is 35±2℃, and the pressure barrel temperature is 47±1℃.
[0080] like Figure 12 and Figure 13 As shown, the salt spray corrosion rate of the large-size high-strength corrosion-resistant magnesium alloy rod finally obtained in Example 1 is only 0.08 mm / y, and has excellent corrosion resistance.
[0081] Example 2:
[0082] A high-strength, corrosion-resistant magnesium alloy, the same as that in Example 1, comprising the following components in percentage by mass:
[0083] Al 8.24wt.%, Zn 0.39wt.%, Mn 0.28wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0084] The large-scale deformation preparation method of the high-strength, corrosion-resistant magnesium alloy is basically the same as that of Example 1, except that the temperature of the rotary forging deformation in step S4 is 200° C. and the total deformation amount is 30%. That is, the specific steps are as follows:
[0085] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0086] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0087] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ60 mm;
[0088] S4. Rotary forging is performed along the radial direction of the extruded bar at 200° C., with the deformation of each pass controlled at 3% and the total deformation at 30%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0089] S5. Perform aging heat treatment on the rotary forging bar at 175° C. and keep the temperature for 72 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0090] like Figure 5 As shown, in Example 2, after rotary forging at 200° C., only a small amount of twin structure appears in the magnesium alloy rod structure, and grain refinement is not obvious.
[0091] like Figure 11 As shown in Table 1, the high-strength corrosion-resistant magnesium alloy bar finally obtained in Example 2 has a yield strength of 364.2 MPa, a tensile strength of 422.1 MPa, an elongation after fracture of 4.61%, and a salt spray corrosion rate of 0.1 mm / y.
[0092] Example 3:
[0093] A high-strength, corrosion-resistant magnesium alloy comprising the following components in percentage by mass:
[0094] Al 6.11wt.%, Zn 0.84wt.%, Mn 0.15wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0095] The large-scale deformation preparation method of the above-mentioned high-strength corrosion-resistant magnesium alloy is basically the same as that of Example 1, except that the grain size of the extruded bar in step S3 is 10-30 μm, the bar diameter is Φ40 mm, the single-pass deformation of the rotary forging deformation in step S4 is 5%, the total deformation is 15.6%, the die rotation speed is 250 rpm, and the aging heat treatment temperature in step S5 is 150° C. and the holding time is 68 h. That is, the specific steps are as follows:
[0096] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0097] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0098] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ40 mm;
[0099] S4. Rotary forging is performed along the radial direction of the extruded bar at 25° C., with the deformation of each pass controlled at 5% and the total deformation at 15.6%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 250 rpm to obtain a rotary forging bar.
[0100] S5. Perform aging heat treatment on the rotary forging bar at 150° C. and keep the temperature for 68 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0101] like Figure 6 As shown, in Example 3, after rotary forging deformation, due to the small total deformation, only a small amount of twin structure appears in the magnesium alloy rod structure, while the single-pass deformation is large and the twin intersection is obvious.
[0102] like Figure 11 As shown in Table 1, the large-size high-strength corrosion-resistant magnesium alloy bar finally obtained in Example 3 has a yield strength of 384.3 MPa, a tensile strength of 398.8 MPa, an elongation after fracture of 2.96%, and a salt spray corrosion rate of 0.09 mm / y.
[0103] Example 4:
[0104] A high-strength, corrosion-resistant magnesium alloy, the same as that in Example 1, comprising the following components in percentage by mass:
[0105] Al 8.24wt.%, Zn 0.39wt.%, Mn 0.28wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0106] The large-scale deformation preparation method of the above-mentioned high-strength corrosion-resistant magnesium alloy is basically the same as that of Example 1, except that the grain size of the extruded bar in step S3 is 10-30 μm, the bar diameter is Φ40 mm, the total deformation amount of the rotary swaging deformation in step S4 is 15.6%, and the aging heat treatment temperature in step S5 is 150° C. and the holding time is 68 hours. That is, the specific steps are as follows:
[0107] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0108] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0109] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ40 mm;
[0110] S4. Rotary forging is performed along the radial direction of the extruded bar at 25° C., with the deformation of each pass controlled at 3% and the total deformation at 15.6%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0111] S5. Perform aging heat treatment on the rotary forging bar at 150° C. and keep the temperature for 68 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0112] like Figure 7 As shown, in Example 4, after rotary forging deformation, due to the small total deformation, only a small amount of twin structure appears in the magnesium alloy rod structure, and the local twins are obviously refined.
[0113] like Figure 11 As shown in Table 1, the large-size high-strength corrosion-resistant magnesium alloy bar finally obtained in Example 4 has a yield strength of 388.2 MPa, a tensile strength of 392.3 MPa, an elongation after fracture of 2.85%, and a salt spray corrosion rate of 0.06 mm / y.
[0114] Comparative Example 1:
[0115] A magnesium alloy comprising the following components in percentage by mass:
[0116] Al 0.032wt.%, Zn 5.62wt.%, Mn 0.08wt.%, Zr 0.76wt.%, impurity element content ≤0.1wt.%, and the balance is Mg.
[0117] The preparation method of the magnesium alloy is substantially the same as that of Example 1, except that the grain size of the extruded bar in step S3 is 10-30 μm, the bar diameter is Φ40 mm, the total deformation amount of the swaging deformation in step S4 is 26.7%, and the aging heat treatment temperature in step S5 is 150° C. and the holding time is 68 h. Specifically, the steps are as follows:
[0118] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0119] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0120] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ40 mm;
[0121] S4. Rotary forging is performed along the radial direction of the extruded bar at 25° C., with the deformation of each pass controlled at 3% and the total deformation at 26.7%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0122] S5. Perform aging heat treatment on the rotary forging bar at 150° C. and keep the temperature for 68 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0123] like Figure 8 As shown, in Comparative Example 1, due to the reduced Al content, the magnesium alloy rod exhibits a bimodal grain structure. After rotary forging, only a small amount of twin structures appear inside the large grains, and the strength performance is poor.
[0124] like Figure 11 As shown in Table 1, the magnesium alloy bar finally obtained in Comparative Example 1 has a yield strength of 283.7 MPa, a tensile strength of 302.4 MPa, an elongation after fracture of 2.67%, and a salt spray corrosion rate of 0.95 mm / y.
[0125] Comparative Example 2:
[0126] A magnesium alloy, the same as that in Example 1, comprising the following components in percentage by mass:
[0127] Al 8.24wt.%, Zn 0.39wt.%, Mn 0.28wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0128] The preparation method of the magnesium alloy is substantially the same as that of Example 1, except that the grain size of the extruded bar in step S3 is 10-30 μm, the bar diameter is Φ40 mm, the total deformation amount of the swaging deformation in step S4 is 6.1%, and the aging heat treatment temperature in step S5 is 150° C. and the holding time is 68 h. Specifically, the steps are as follows:
[0129] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0130] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0131] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ40 mm;
[0132] S4. Rotary forging is performed along the radial direction of the extruded bar at 25° C., with the deformation of each pass controlled at 3% and the total deformation at 6.1%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0133] S5. Perform aging heat treatment on the rotary forging bar at 150° C. and keep the temperature for 68 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0134] like Figure 9 As shown, in Comparative Example 2, after rotary forging deformation, due to the small total deformation, only a very small amount of twin structure appears in the magnesium alloy bar structure, and the strength improvement is not obvious.
[0135] like Figure 11 As shown in Table 1, the magnesium alloy bar finally obtained in Comparative Example 2 has a yield strength of 301.3 MPa, a tensile strength of 307.5 MPa, an elongation after fracture of 4.22%, and a salt spray corrosion rate of 0.12 mm / y.
[0136] Comparative Example 3:
[0137] A magnesium alloy, the same as that in Example 1, comprising the following components in percentage by mass:
[0138] Al 8.24wt.%, Zn 0.39wt.%, Mn 0.28wt.%, impurity element content ≤0.06wt.%, and the balance is Mg.
[0139] The preparation method of the magnesium alloy is substantially the same as that of Example 1, except that the grain size of the extruded bar in step S3 is 10-30 μm, the bar diameter is Φ40 mm, the swaging deformation temperature in step S4 is 300° C., the total deformation is 6.1%, and the aging heat treatment temperature in step S5 is 150° C., and the holding time is 68 h. Specifically, the steps are as follows:
[0140] S1. After melting the simple substances of each element in a smelting furnace according to the proportion, the temperature is raised to 730°C and fully stirred. The speed is controlled at 650 rpm, the time is controlled at 13 minutes, and the mixture is kept at a temperature of 40 minutes. Then, a refining agent is added at 720°C for refining, degassing and deslagging. The refining agent is calcium chloride (CaCl2). The ratio of the mass of calcium chloride to the total mass of the simple substances of each element is controlled at 1:50. The time is controlled at 10 minutes. The mixture is kept at a temperature of 40 minutes, and the molten metal is cast to obtain an ingot.
[0141] S2. Perform homogenization heat treatment on the ingot at 400°C for 8 hours;
[0142] S3. Coating the surface of the ingot with graphite oil, placing it in a heating furnace together with a hot extrusion die and heating it to 400° C. for preheating treatment, keeping it warm for 2 hours, and then hot extruding the ingot, controlling the extrusion ratio to 20:1 and the profile extrusion speed to 0.4 mm / s. After the hot extrusion is completed, air cooling is performed to room temperature to obtain an extruded rod with a grain size of 10-30 μm and a rod diameter of Φ40 mm;
[0143] S4. Rotary forging is performed along the radial direction of the extruded bar at 300° C., with the deformation of each pass controlled at 3% and the total deformation at 6.1%. The forging speed is 2000 times / min, the feed speed is 1.5 m / min, and the die rotation speed is 200 rpm to obtain a rotary forging bar.
[0144] S5. Perform aging heat treatment on the rotary forging bar at 150° C. and keep the temperature for 68 hours to obtain a high-strength, corrosion-resistant magnesium alloy bar.
[0145] like Figure 10 As shown, in Comparative Example 3, after being subjected to rotary forging deformation at a relatively high heating temperature, the magnesium alloy rod exhibits a uniform recrystallized structure without obvious twins due to dynamic recrystallization.
[0146] like Figure 11 As shown in Table 1, the magnesium alloy bar finally obtained in Comparative Example 3 has a yield strength of 315.3 MPa, a tensile strength of 320.2 MPa, an elongation after fracture of 7.21%, and a salt spray corrosion rate of 0.15 mm / y.
[0147] A comprehensive comparison of different embodiments and comparative examples shows that when the swaging deformation temperature is higher (Example 2), the plastic deformation ability of the magnesium alloy bar is improved, but the number of twins in the structure is small, the deformation strengthening is weak, and the corrosion resistance is poor.
[0148] When the swaging deformation temperature is higher than the range of the present invention (Comparative Example 3), due to the occurrence of dynamic recrystallization, there is no twin structure inside the magnesium alloy bar structure, and the strength and corrosion resistance are too poor;
[0149] The room temperature rotary forging deformation performed under a larger single-pass deformation amount (Example 3) and a smaller total deformation amount (Example 4) results in a smaller strain accumulation, a smaller number of twins in the magnesium alloy bar structure, unobvious grain refinement, weak deformation strengthening, and poor corrosion resistance;
[0150] When the total deformation is lower than the range of the present invention (Comparative Example 2), the number of twins in the magnesium alloy rod structure is even smaller, and the strength and corrosion resistance are too poor;
[0151] The alloy composition with lower Al content (Comparative Example 1) has less second phase precipitation during aging, less precipitation strengthening, and poor strength.
[0152] However, Example 1 adopts an alloy composition ratio with a higher Al content, a more appropriate rotary forging deformation and a post-forging aging heat treatment process, and has the best comprehensive performance.
[0153] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
Claims
1. A large-size high-strength corrosion-resistant magnesium alloy, characterized in that: The magnesium alloy comprises the following components in percentage by mass: Al 5-10wt.%, Zn 0.1-3wt.%, Mn 0.05-0.5wt.%, impurity element content ≤ 0.1wt.%, balance Mg; The magnesium alloy ingot is subjected to hot extrusion forming, rotary forging deformation and aging heat treatment to obtain a large-size high-strength corrosion-resistant magnesium alloy.
2. A method for preparing a large-size, high-strength, corrosion-resistant magnesium alloy as claimed in claim 1, characterized in that: The method comprises the following steps: S1, after melting the raw materials of each element, stirring, standing and keeping warm, then refining, standing and keeping warm again, and then casting the molten metal to obtain an ingot; S2, homogenizing heat treatment of the ingot and keeping it warm; S3, preheating the ingot, keeping it warm, and then hot extruding it to obtain an extruded rod; S4, performing rotary forging deformation along the radial direction of the extruded bar to obtain a rotary forging bar; S5. Perform aging heat treatment on the rotary forging bar to obtain a large-size high-strength corrosion-resistant magnesium alloy.
3. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: In step S1, the stirring temperature is 700-760° C., the rotation speed is 500-800 rpm, the time is 5-20 min, and the standing time is 20-60 min.
4. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The refining temperature in step S1 is 700-740° C., the added refining agent is selected from one or more of calcium chloride, barium chloride, calcium fluoride, and barium fluoride, the ratio of the mass of the added refining agent to the total mass of the raw materials of each element is 1:(30-70), the refining time is 5-15 minutes, and the standing time is 20-60 minutes.
5. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The temperature of the homogenization heat treatment in step S2 is 380-420° C., and the insulation time is 2-24 hours.
6. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The temperature of the preheating treatment in step S3 is 380-420° C., and the insulation time is 1-4 hours.
7. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The temperature of hot extrusion in step S3 is 380-420° C., the extrusion ratio is (5-70):1, and the profile extrusion speed is 0.2-2 mm / s.
8. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The grain size of the extruded rod in step S3 is 5-50 μm, and the rod diameter is Φ30-120 mm.
9. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: In step S4, the temperature of rotary forging deformation is 10-250°C, the deformation amount of a single pass is 1-8%, the total deformation amount is 10-45%, the forging speed is 1000-3000 times / min, the feed speed is 1-3m / min, and the mold rotation speed is 150-300rpm.
10. The method for preparing a large-size high-strength corrosion-resistant magnesium alloy according to claim 2, characterized in that: The temperature of the aging heat treatment in step S5 is 100-200° C., and the insulation time is 24-100 hours.
Citation Information
Patent Citations
Medical degradable multi-element Mg-Zn-Y-Ca-Zr alloy with high strength and toughness and corrosion resistance, and preparation method thereof
CN107236886A
High-toughness Mg-Al-La-Gd-Zr heat-resistant magnesium alloy and preparation method thereof
CN117947323A
Cited By
Method for preparing magnesium alloy through low-temperature rotary swaging
CN121131624A